Pernanan pajak restoran terhadap pendapatan asli daerah pada Kabupaten Timor Tengah Selatan - Deby Ritmy Yumiaty Benu; Wulan Dri Puspita (Jurnal Ilmiah Bisnis dan Perpajakan (Bijak), 2022)
This study aims to determine how big the contribution of restaurant taxes and the effectiveness of restaurant tax revenues in Timor Tengah Selatan Regency to Regional Original Income from 2017 to 2020. The method used in this research is descriptive quantitative by describing the data in sentence form according to the occurred in Timor Tengah Selatan Regency in the form of restaurant tax. The source of the data used is secondary data in the form of a report document on the realization of restaurant tax revenues and PAD. As a result, the contribution of restaurant tax to PAD still fluctuates every year with a tendency to fall. While the level of effectiveness of the restaurant tax every year can be said to be very effective, even though in 2020 the effectiveness value decreased drastically.